Frekuensi ANC dan Ketidakpatuhan Minum TTD sebagai Faktor Risiko Terjadinya Anemia pada Ibu Hamil Trimester III: The Frequency of ANC and Non-adherence to Taking Iron Tablets as Risk Factors for Anemia in Third-Trimester Pregnant Women - Yeni Sriwahyuni; Ria Purnawian Sulistiani; Agus Sartono; Purwanti Susantini (UNIVERSITAS NGUDI WALUYO, 2024)
Anemia in pregnant women at the Cikedung Indramayu Community Health Center has increased in 2021 from 8.04% to 14.98%. Third trimester pregnant women are at risk of experiencing anemia. Anemia in pregnant women can influence the incidence of low birth weight. Anemia in pregnant women is influenced by the age of the pregnant woman, the quality of ANC, the nutritional status of the mother and consumption of blood supplement tablets. The aim of this study was to determine the risk factors for anemia in third trimester pregnant women at the Cikedung Community Health Center. This research method is analytical observational with a case control study design. The research sample of third trimester pregnant women was 106 people consisting of 53 cases and 53 controls. The case sampling technique used inclusion and exclusion criteria, while the control sample was matched for gestational age and random. Bivariate analysis using Chi-Square test and risk (OR). Chi Square analysis shows that the age of pregnant women (p-value 0.680) and the nutritional status of pregnant women with Chronic Energy Deficiency (p-value 0.235) are not risk factors for anemia in third trimester pregnant women, while the frequency of ANC is less than 6x (p-value 0.037; OR: 9.244) and non-compliance with taking TTD (p-value 0.000; OR: 8.135) as risk factors for anemia in third trimester pregnant women. ANC frequency of less than 6 times and non-compliance with taking TTD are risk factors for anemia in third trimester pregnant women. ABSTRAK Anemia pada ibu hamil di Puskesmas Cikedung Indramayu mengalami peningkatan pada tahun 2021 dari 8,04% menjdi 14,98%. Ibu hamil trimester III beresiko mengalami anemia. Anemia pada ibu hamil dapat mempengaruhi kejadian Berat Badan Lahir Rendah. Anemia pada ibu hamil dipengaruhi umur ibu hamil, kualitas ANC, status gizi ibu dan konsumsi Tablet Tambah Darah. Tujuan penelitian ini adalah untuk mengetahui faktor risiko anemia ibu hamil trimester III di Puskesmas Cikedung. Metode penelitian ini adalah observasional analitik dengan desain studi case control. Sampel penelitian ibu hamil trimester III sebanyak 106 orang terdiri dari 53 kasus dan 53 kontrol.Teknik pengambilan sampel kasus dengan kriteria inklusi dan ekslusi, sedangkan sampel kontrol dilakukan matching umur kehamilan dan random. Analisis secara bivariat dengan uji Chi-Square dan besar risiko (OR). Analisis Chi Square menunjukkan bahwa umur ibu hamil (p-value 0,680) dan status gizi ibu hamil KEK (p-value 0,235) bukan faktor risiko anemia ibu hamil trimester III, sedangkan frekuensi ANC kurang dari 6x (p-value 0,037; OR: 9,244) dan ketidakpatuhan minum TTD (p-value 0,000; OR:8,135) sebagai faktor risiko anemia ibu hamil trimester III. Frekuensi ANC kurang dari 6x dan ketidak patuhan minum TTD sebagai faktor risiko terjadinya anemia pada ibu hamil trimester III.